Evaluation of Expediency of Using Industrial Outsourcing in Industrial Enterprise - I. Farkhoutdinov, Il'nur; G. Isavnin, Aleksei (International Journal of Engineering and Technology, 2018)
One of the main criteria of successful application of industrial outsourcing is competent definition of degree of expediency of use of this tool at the enterprise. Weighing possibilities of development of own production with opportunities of application of resources of outsourcers, the management of the company closely approaches the solution of a task "make or buy".It should be noted that transition to outsourcing can be considered expedient if thus the enterprise gains certain competitive advantages and achieves goals. Reasonable combination of outsourcing and insourcing where management of them is constructed on in advance defined accurate principles, and identification of exact borders of outsourcing are pledge of effective application of this model of management at the enterprise. Therefore at the solution of a task "make or buy" the management of the company needs to weigh carefully all pros and cons, and also to consider experience of use of this or that tool by other enterprises, including competitors.Definition of exact borders of outsourcing and process of transition to this model of management includes a set of procedures which carrying out is necessary for identification of a real situation, and also opportunities of the enterprise when carrying out optimization.The purpose of this work is development of a technique of an assessment of expediency of application of industrial outsourcing.Â Â